PRAGMATIC FEATURES IN THE SPEAKING SECTIONS OF BAHASA INGGRIS UNTUK SMA/MA KELAS XI SEMESTER 1 - Dewi Rosaria Indah (Widya Mandala Surabaya Catholic University, 2015)
One of the 21st century challenges is effective oral communication. While at the same time, some senior high school students are considered to be inept to speak English fluently. Their shortcomings in speaking belong to area of pragmatics. This study was intended to evaluate an English course book for senior high school entitled Bahasa Inggris untuk SMA/MA Kelas XI Semester 1 that is widely used by most senior high schools in Surabaya. Based on those rationales, this study investigated Bahasa Inggris untuk SMA/MA Kelas XI Semester 1 to find out what language function is taught and how the language function is delivered as reflected by the four pragmatic features in the speaking sections in the course book under study. The result of the study found first that there were all 8 language functions that were under transactional and interpersonal functions as demanded by the Curriculum 2006 but they were not presented in sequence as what the Curriculum 2006 demanded. Second, that all the four pragmatic features: context, the cooperative principles, and speech acts and politeness were found in the speaking sections and yet two characteristics in Speech Acts were not found. 5 items in Speech Acts and Politeness were not found as well. The arrangement of the four pragmatic features were provided moderately and mostly implied while they should be provided explicitly. Key Words: pragmatic features, language function, speaking sections, context, the cooperative principles, speech acts, politeness, senior high school English course book.